Molecular mechanisms of Methylorubrum extorquens DSM13060, a growth-promoting endosymbiont of pine, for developing improved future biofertilizers - Baruah, Namrata; Oulun yliopisto (Acta Universitatis Ouluensis, ISSN 1796-220X, 2024)
Endophytic bacteria reside within the living tissues of plants and are an important component in plant microbiome. They promote plant tolerance to fluctuating environmental conditions along with growth and development, which is a focal point in enhancing crop production. This study aims to understand the mechanisms of an endosymbiont Methylorubrum extorquens DSM13060, which thrives inside the meristematic tissues of Scots pine (Pinus sylvestris L.) providing advantages to the host. M. extorquens DSM13060 does not produce any common phytohormones for plant growth promotion. During their entry, they consume pine-derived methanol to produce poly-3-hydroxybutyrate (PHB). This compound provides protection against oxidative stress for both the endosymbiont and the host through its fragments, methyl-esterified 3-hydroxybutyrate (ME-3HB) oligomers. I have analyzed the involvement of genes in the production of ME-3HB oligomers and thereby host colonization. Gene deletions of PHB depolymerase (phaZ1), synthase (phaC), and transcription factor (phaR) showed the importance of PHB metabolism for host colonization by M. extorquens DSM13060. This study also revealed their capacity to employ an ankyrin-repeat protein, Ank_2, to manipulate the host nuclear processes. It has a unique capacity to accumulate intracellularly around host nuclei. This was hampered by the deletion of the Ank_2 gene, which affected both colonization and growth promotion in pine. A yeast two-hybrid assay showed that Ank_2 interacts with an extracellular plant cell wall degrading enzyme GH17b and nuclear proteins BCCIP, BZIP49, and NUP54, which affect the success of colonization and plant development. The high-resolution secondary ion mass spectrometry (NanoSIMS) study showed the ability of the endosymbiont to transfer carbon and nitrogen-based compounds to the pine meristematic cells. This study complements the picture of the endosymbiosis of M. extorquens DSM13060 with Scots pine by interconnecting the different levels of the interaction. In this unique endosymbiosis, PHB metabolism is required for entry, Ank_2 is the key component for successful colonization, and the exchange of compounds during the interaction portrays the mutualism of endosymbiosis. My study on Scots pine and M. extorquens DSM13060 interaction has given a new outlook on symbiotic associations in plants and encourages the use of endosymbionts as future biofertilizers.
Keywords: Scots pine; Plant-microbe relationships : Molecular aspects; Growth (Plants); Endosymbiosis; Endophytes; Methylobacterium; Poly-beta-hydroxybutyrate; Plant colonization; Transcription factors; Oxidative stress; Biofertilizers; metsämänty; kasvu; endofyytit; bakteerit; transkriptiotekijät; metanoli; oksidatiivinen stressi; lannoitteet